ANTIOXIDANT PROFILE AND PHYTOCHEMICAL CONTENT OF DIFFERENT PARTS OF SUPER RED DRAGON FRUIT (HYLOCEREUS COSTARICENSIS) COLLECTED FROM WEST JAVA-INDONESIA - Fidrianny, Irda; Ilham, Nadia; Hartati, Rika (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: The goals of this research were to observe antioxidant properties from different parts of super red dragon fruit (Hylocereus costaricensis) using two antioxidant testing methods which were 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) (ABTS). Methods: Antioxidant activities were determined using DPPH and ABTS assays, total phenolic content (TPC) using Folinâ€“Ciocalteu reagent, flavonoid content by Chang's method. Results: Inhibitory concentration 50% (IC50) of DPPH scavenging activity of all of the extracts in the range of 2.69 Î¼g/ml was âˆ’94.17 Î¼g/ml. The ethyl acetate peel extract of super red dragon fruit expressed the highest TPC (4.56 g GAE/100 g) and the highest total flavonoid content (12.63 g QE/100 g). TPC in flesh extract of super red dragon fruit had a negative and significant correlation with their IC50 of ABTS. The IC50 of DPPH and IC50 of ABTS of flesh extract of super red dragon fruit showed positive and significant correlation. Conclusion: All different parts extracts of super red dragon fruit (except n-hexane flesh extract) were categorized as a very strong antioxidant by DPPH method. Phenolic compounds in flesh extract of super red dragon fruit were the major contributor in antioxidant activities by ABTS method. DPPH and ABTS showed linear results in antioxidant activities of super red dragon fruit flesh extract.